What Goliaths and Davids among Swiss firms tell us about expected returns on Swiss asset markets - David R. Haab; Thomas Nitschka (Swiss Journal of Economics and Statistics, 2019)
Motivated by recent US evidence, we evaluate the predictive power of changes in the weight of large firms in the aggregate stock market ("Goliath vs David" (GVD)) for Swiss stock market returns and bond market returns. Previous research suggests that the asset return dynamics in the US and Switzerland differ markedly. Forecasting Swiss asset returns hence constitutes a challenging "out-of-sample" test for GVD. Over the sample period from January 1999 to December 2017, we find that the Swiss version of GVD exhibits predictive power for Swiss stock and bond market returns even in the presence of global predictors. However, Swiss bond market returns are best predicted by the US term spread.
Keywords: G15; G17; 330; Bond market predictability; Risk premium; Stock market